Assessment of Urban Landscape Patterns to Measure the Effects of Urbanization on Landscape Structure (Case Study: Kermanshah City) - Gholam Reza Sabzghabaei; Soolmaz Dashti; Kaveh Jafarzadeh; Mojgan Bazmara Baleshti (جغرافیا و پایداری محیط)
1-Introduction The evolution of the spatial structure of a city is the result of economic-socio factors and natural (Tian et al., 2011). Today, urbanization in the developing countries and developed with an unprecedented growth is on the rise (Kazemi Pour and Hajian, 2011, United Nations Report 2008). This rapid and uncontrolled growth in cities, numerous changes in structure and function to do landscape (Solon, 2009). Quantifying these patterns and their changes will be very useful for sustainable urban development. Recently spatial metric in urban environments, due to their ability to demonstrate the spatial components of landscape structure, and process dynamics of environmental degradation and urbanization growth are used to overcome management problems (Porter Bolland, 2007). 2- Materials and Methods In this study, satellite images Land sat 8 and 7 Sensor OLI and ETM+ geo_ reference were used for the preparation of map of the Earth's surface and analyzing the changes, respectively. That The first, preprocessing operations including geo_ referencing was performed on the images. In the next step (step processing) primary land use was marked. That human land use, wasteland and without cover, tree cover, agricultural and water according to the understanding of the area. Then the images were classified with maximum likelihood method by software ENVI 4/7 and land use map was prepared. Next step, kappa coefficient was calculated to verify the accuracy of image classification, using test samples, the accuracy of the statistical parameters. In the final step raster map of land-use Enter the software FRAGSTATS 4.2 and metrics CA NP,TE ,MPS, PLAND, Shape-MN, ENN-MN, LPI, PD, LSI ,IJI وED were studied. 3- Results and Discussion Residential area has increased to 3304 hectares during the period of the study which is caused by the increase of Kermanshah population. But other users have a decreasing trend, in which wasteland and without cover the 2492 hectares have more reduction. Due to lower sales of agricultural and horticultural land and lack of economic efficiency of the industry, drop margins of agricultural land lead to drought because most of Kermanshah dry land cultivation and development projects for the social welfare of population growth and migration due to be built. But due to neglecting natural resources and urban infrastructure destroyed and turned into wasteland and without cover these projects is very much. . Also, according to the results of the analysis metrics landscape has an increasein Residential User Metrics PLAND, NP, PD, LPI, TE. Farmer User has an increase in three Metrics MPS To the) 42/81 Hectare(, Shape- MN to the (0/03 Hectare) and ENN-MN to the (10/48 Hectare). Users without coverage have an increase Only Metrics MPS, TE, ED, LSI and Shape-MN. Tree cover in the five Metrics) NP, PD, LSI, IJI) increases while other metrics have decreased. The blue zone has increased only metric TE to the 81870 Meter. 4- Conclusion According to the results Increased population growth and urbanization in the region during the period under review, make man-made stains in this area increase while with the expansion of human development, the percentage of bare lands has decreased. The area of stains agricultural and barren are also a lot of changes and addition the number and size of applications has also changed which caused destruction and annihilation of agricultural land in the immediate boundaries of urban. It is matter caused changes in the composition and distribution of the urban landscape, that increasing human activities. At the natural environment and urban development, the destruction of the natural environment and tend to take a more spots which is a sign of increased human activity in the region and increasing destruction of nature in the city. Also in Kermanshah city, the texture fine-grained urban with too little distance between them is urban landscape which was lost. As well as reducing the number of stains and increase the distance between stains on the one hand and lack of proper distribution stains on the other hand reason reduce connection and bond between uses the urban environment.